Diversidade e densidade ictiofaunística em lagos de várzea da Reserva de Desenvolvimento Sustentável Mamirauá, Amazonas, Brasil - CHAVES, Rose Cristine Queiroz (Universidade Federal do Pará, 2014)
The structure of the fish community in amazonian várzea lakes is determined by the flood pulse and seasonal and daily variations in the physico-chemical parameters of the water. The objective of this work was to characterize the fish community structure of four lakes in different stages of the seasonal cycle. Fish samples were taken bimonthly along one year in four lakes at Mamirauá Sustainable Development Reserve, state of Amazonas, Brazil. The richness of species and the fish biomass were analyzed, in order to investigate how much the community patterns were regulated by the environmental variables. A total of 6,058 individual fish were collected, representing 6 orders, 21 families, 76 genera and 116 species. The orders Characiformes and Siluriformes presented the largest variety of families and species, reaching together around 90% of the captured specimens. The fish fauna varied between different periods and lakes, and the highest richness and biomass values were found in the water level dropping season, except in Taracoá Lake with greater richness in the flooding season. The species Potamorhina latior, Potamorhina altamazonica, Mylossoma duriventre, Amblydoras hancokii, Amblydoras sp., Liposarcus pardalis, Psectrogaster amazonica and Osteoglossum bicirrhosum showed the highest number of individuals. Oxydoras niger, Colossoma macropomum, Cichla monoculus, Osteoglossum bicirrhosum, Arapaima gigas and Pseudoplatystoma tigrinum were the dominant species in biomass. The analysis of the physico-chemical parameters indicates that the changes along the year and the flood pulse influence determine the fish community structure, and the set of parameters composed by dissolved oxygen, pH and water temperature seemingly explains the fish community pattern. Similarity Analysis indicates that the fish fauna composition in the same time of the flood pulse in consecutive years are much alike. Therefore, it is probable that the fish community composition is re-established every cycle, with the connection of the different water bodies during the flood.